2019
DOI: 10.1002/pon.5187
|View full text |Cite
|
Sign up to set email alerts
|

Self‐compassion and hope in the context of body image disturbance and distress in breast cancer survivors

Abstract: Objective: Greater hope and self-compassion have individually been associated with lower psychological distress in women with breast cancer. Self-compassion is also associated with lower body image distress in this population, yet it is unknown whether hope also has this association. This study aimed to investigate the extent to which hope accounts for body image distress and psychological distress in breast cancer survivors alone, and in direct comparison to self-compassion. Method:A total of 195 women were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 33 publications
7
45
1
Order By: Relevance
“…This initial resistance to being self-compassionate has previously been addressed using psychoeducation (Gilbert & Procter, 2006 ), which may be a critical component to be incorporated into future applications of the MyCB intervention approach. Psychoeducation dispelling myths and fears around treating oneself self-compassionately may be particularly helpful for improving adherence among younger BCSs, who tend to report lower self-compassion (Przezdziecki et al, 2013 ; Przezdziecki & Sherman, 2016 ; Todorov, Sherman, & Kilby, 2019 ), perhaps due to a fear of being self-compassionate. Alternatively, an intervention which more directly addresses the importance that younger BCSs place on physical appearance for their self-worth (self-evaluative salience), may be more beneficial for younger BCSs, who typically struggle with this evaluative component of body image (Moreira & Canavarro, 2010 ; Sherman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…This initial resistance to being self-compassionate has previously been addressed using psychoeducation (Gilbert & Procter, 2006 ), which may be a critical component to be incorporated into future applications of the MyCB intervention approach. Psychoeducation dispelling myths and fears around treating oneself self-compassionately may be particularly helpful for improving adherence among younger BCSs, who tend to report lower self-compassion (Przezdziecki et al, 2013 ; Przezdziecki & Sherman, 2016 ; Todorov, Sherman, & Kilby, 2019 ), perhaps due to a fear of being self-compassionate. Alternatively, an intervention which more directly addresses the importance that younger BCSs place on physical appearance for their self-worth (self-evaluative salience), may be more beneficial for younger BCSs, who typically struggle with this evaluative component of body image (Moreira & Canavarro, 2010 ; Sherman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, arts-based approaches involving creative arts therapy and arts medicine showed strong effects on the mental health of women living with breast cancer or gynecological cancer [ 36 ]. According to another study, self-compassion and hope-focused therapy may be useful to relieve body image dissatisfaction in patients with breast cancer [ 37 ]. In the same vein, psychologists at Macquarie University in Sydney have developed a program called “My Changed Body”, which is a web platform containing writing exercises to encourage compassion and minimize mental distress related to body image dissatisfaction in women with breast cancer [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies focused on a range of physical health conditions (Table 1). Five studies used breast cancer samples (Brown et al 2020;Przezdziecki and Sherman 2016;Przezdziecki et al 2013;Sherman et al 2017;Todorov et al 2019), three non-breast cancers (Gillanders et al 2015;Schellekens et al 2017;Zhu et al 2019), three diabetes (Friis et al 2015;Morrison et al 2019;Ventura et al 2019) (Eller et al 2014;Kemppainen et al 2013a, b;Williams et al 2019;Zhu et al 2019). Eleven studies (Eller et al 2014;Kemppainen et al 2013a, b;Friis et al 2015;Gillanders et al 2015;Harrison et al 2017;Morrison et al 2019;Przezdziecki et al 2013;Schellekens et al 2017;Sherman et al 2017;Williams et al 2019;Ventura et al 2019;Zhu et al 2019) reported time since diagnosis, which ranged from less than 1 week to an average of 16.70 years.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…As shown in Table 2, age, gender and illness duration were most frequently controlled, whilst two studies controlled coping styles Pinto-Gouveia 2011, 2013;Gillanders et al 2015). After controlling for potential covariates, five of these studies Pinto-Gouveia 2011, 2013;Eller et al 2014;Kemppainen et al 2013a, b;Todorov et al 2019;Ventura et al 2019;Zhu et al 2019) found significant, inverse associations between self-compassion and anxiety, with values ranging from β = −.21 to β = −.53. Six studies examined the relationship between depression and self-compassion using multivariate analyses.…”
Section: Multivariate Analysesmentioning
confidence: 99%
See 1 more Smart Citation